Systems-Wide Analysis of Acclimation Responses to Long-Term Heat Stress and Recovery in the Photosynthetic Model Organism Chlamydomonas reinhardtii . Issue 11 (18th November 2014) - Hemme, Dorothea; Veyel, Daniel; Mühlhaus, Timo; Sommer, Frederik; Jüppner, Jessica; Unger, Ann-Katrin; Sandmann, Michael; Fehrle, Ines; Schönfelder, Stephanie; Steup, Martin; Geimer, Stefan; Kopka, Joachim; et al.
Abstract : Early acclimation responses of Chlamydomonas to long-term heat stress are directed toward restoration of protein homeostasis and membrane fluidity involving the redirection of photosynthetic electron flow from carbon fixation to saturated fatty acid synthesis, while late responses deal with the depletion of electron sinks. During recovery, cells aim at a rapid resumption of cell division/growth. Abstract: We applied a top-down systems biology approach to understand how Chlamydomonas reinhardtii acclimates to long-term heat stress (HS ) and recovers from it. For this, we shifted cells from 25 to 42°C for 24 h and back to 25°C for ≥8 h and monitored abundances of 1856 proteins/protein groups, 99 polar and 185 lipophilic metabolites, and cytological and photosynthesis parameters. Our data indicate that acclimation of Chlamydomonas to long-term HS consists of a temporally ordered, orchestrated implementation of response elements at various system levels. These comprise (1) cell cycle arrest; (2) catabolism of larger molecules to generate compounds with roles in stress protection; (3) accumulation of molecular chaperones to restore protein homeostasis together with compatible solutes; (4) redirection of photosynthetic energy and reducing power from the Calvin cycle to the de novo synthesis of saturated fatty acids to replace polyunsaturated ones in membrane lipids, which are deposited in lipid bodies; and (5) when sinks for photosynthetic energy and reducing power are depleted, resumption of Calvin cycle activity associated with increased photorespiration, accumulation of reactive oxygen species scavengers, and throttling of linear electron flow by antenna uncoupling. During recovery from HS, cells appear to focus on processes allowing rapid resumption of growth rather than restoring pre-HS conditions.